Change in Depression, Confidence, and Physical Function Among Older Adults With Mild Cognitive Impairment. Issue 3 (July 2019) - Ellis, Jennifer L.; Altenburger, Peter; Lu, Yvonne
Abstract : Background and Purpose: Nearly a quarter of those in the United States older than 71 years experience mild cognitive impairment. Persons with mild cognitive impairment battle depression and progressive disengagement from daily activities, which contribute to participation restriction and activity limitation. Daily engagement in meaningful activity (DEMA) is a tailored intervention designed to benefit persons with mild cognitive impairment and their caregivers through preserved engagement and supported adjustment to cognitive changes. This secondary analysis was guided by the International Classification of Functioning, Disability and Health (ICF) model. Aims were to (i) explore the extent to which change in self-rated activity performance and physical function can predict change in depressive symptoms, (ii) evaluate for difference in confidence and depressive symptoms at ICF levels of activity and participation, and (iii) quantify the impact of daily engagement at the ICF level of participation on physical function. Methods: A secondary analysis was conducted using data from the parent study, which was a 2-group randomized trial involving persons with mild cognitive impairment and their informal caregivers participating in the Indiana Alzheimer Disease Center DEMA program. Quantitative analysis (dyads: DEMA N = 20, Information Support N = 20) examined outcomes at posttest and follow-up. Analysis employed linear regression to model the relationship between explanatory and dependent variables and independent t test to examine for difference in confidence, depression, and physical function. Results and Discussion: At posttest, change in self-rated performance predicted change in depressive symptoms. Those in the DEMA group who engaged in activity at the ICF level of participation demonstrated a significant increase in confidence and physical function. Although not significant, the control group posttest results showed a mean decrease in confidence. Conclusions: Results demonstrate a positive impact of DEMA on depressive symptoms, confidence, and physical function. Change in occupational performance predicted change in depressive symptoms. Confidence significantly improved among those who engaged at the ICF participation level. A larger, randomized controlled longitudinal trial is needed to better assess the impact of DEMA on physical function, activity, participation restriction, and quality of life.